Neurotoxins 2018
DOI: 10.5772/intechopen.69431
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxins and Autism

Abstract: Recently, a great concern has risen about the increasing prevalence of autism as a neurodevelopmental disorder. Environmental factors as significant contributors to children's health through a wide range of routes are linked to remarkable increases in this disorder. It is well known and accepted that young children are more vulnerable to environmental toxins, compared to adults. Modern day lifestyles with more mercury and lead exposures, fast food, cell phones, and microwaves place children at higher risk of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 115 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…It gives metabolic products to release energy and contributes to the conversion of linoleic acid to acronic acid, It was also found that vitamin B6 may prevent elevated homocysteine levels in the blood, which is associated with an increased risk of cardiovascular disease, which also accelerates arterial disease [6] . Glycerrhiza is one of the legume family plants, Glycyrrhizin glubara is considered to be the most important and best species because it is rich in the active substance with a sweet taste called glycyrrhizin [7], [8] , in addition to glucose,it is 40 times as sweet as sugar cane [9]. Glycerrhiza is rich in many chemical compounds such as, glycyrrhizin, flavonoids, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It gives metabolic products to release energy and contributes to the conversion of linoleic acid to acronic acid, It was also found that vitamin B6 may prevent elevated homocysteine levels in the blood, which is associated with an increased risk of cardiovascular disease, which also accelerates arterial disease [6] . Glycerrhiza is one of the legume family plants, Glycyrrhizin glubara is considered to be the most important and best species because it is rich in the active substance with a sweet taste called glycyrrhizin [7], [8] , in addition to glucose,it is 40 times as sweet as sugar cane [9]. Glycerrhiza is rich in many chemical compounds such as, glycyrrhizin, flavonoids, etc.…”
Section: Introductionmentioning
confidence: 99%